Anti-Inflammatory Activity of the Compositae Family and Its Therapeutic Potential - Lopes, Deise Cristina Drummond Xavier Paes; de Oliveira, Temistocles Barroso; Viçosa, Alessandra Lifsitch; Valverde, Simone Sacramento; Ricci Júnior, Eduardo (Planta Medica, 2020)
Compositae is the largest family of flowering plants, with more than 1600 genera and 22 000 species. It has many economic uses in foods, cosmetics, and pharmaceutics. The literature reports its numerous medicinal benefits and recognized anti-inflammatory activity. Thus, this study evaluated the technological trends of anti-inflammatory activity of Compositae, based on the survey of scientific databases, articles, and patents, as well as the website of the Brazilian National Health Regulatory Agency (ANVISA), which is responsible for registering and controlling of healthcare and cosmetic products in the Brazil. The survey was conducted between 2008 and 2018, in the databases Science Direct, Lilacs, PubMed, and Web of Science (main collection), as well as the SciELO Citation Index. The patent survey was carried out on the basis of the Derwent Innovations Index, an important source for worldwide patent consultation, which covers 20 y of registered patents. Despite the numerous studies involving species of the Compositae family in different models of anti-inflammatory activity, there are few records of patents or products on the market from these species for that purpose. Some species have a traditional use and are present even in the Phytotherapic Summary of the Brazilian Pharmacopeia. This review confirms the therapeutic potential of Compositae for the development of anti-inflammatory drugs and reinforces the need to develop competencies and reduce technological bottlenecks to promote research and innovation in biodiversity products.
Keywords: Compositae; anti-inflammatory activity; research; patents; products